2014
DOI: 10.1016/j.radonc.2014.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Creating a data exchange strategy for radiotherapy research: Towards federated databases and anonymised public datasets

Abstract: Disconnected cancer research data management and lack of information exchange about planned and ongoing research are complicating the utilisation of internationally collected medical information for improving cancer patient care. Rapidly collecting/pooling data can accelerate translational research in radiation therapy and oncology. The exchange of study data is one of the fundamental principles behind data aggregation and data mining. The possibilities of reproducing the original study results, performing fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
67
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 89 publications
(71 citation statements)
references
References 20 publications
0
67
0
1
Order By: Relevance
“…Recently, Skripcak et al 16 reported on challenges and possible solutions for the strategic development of international research data exchange framework in radiation therapy and oncology and identified three major classes of data-pooling models: centralized, decentralized and hybrid. Our approach used a decentralized model in which data are collected, validated and processed at the designated RTTQA centre by expert trial QA staff.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Skripcak et al 16 reported on challenges and possible solutions for the strategic development of international research data exchange framework in radiation therapy and oncology and identified three major classes of data-pooling models: centralized, decentralized and hybrid. Our approach used a decentralized model in which data are collected, validated and processed at the designated RTTQA centre by expert trial QA staff.…”
Section: Discussionmentioning
confidence: 99%
“…De nouvelles approches sont donc nécessaires afin de générer des études de bon niveau de preuve, et l'une de ces approches est la constitution et l'exploitation de bases de données massives détaillées, intégrant un grand nombre de paramètres [3]. Au sein de ces données, la biologie moléculaire et la génomique sont appelées à jouer un rôle prépondérant.…”
Section: Introductionunclassified
“…As indicated in a recent study, radiation oncology specialty is a top offender for exceeding the sustainable growth rate (SGR) target, with its excess expenditures from 2003 to 2009 hovering at 300% range as compared to 2002 [8]. To mitigate negative impact of Medicare cuts on cancer patents and radiation oncology specialty, big data can be exploited to improve treatment efficacy, optimize therapeutic ratio as well as personalize treatment options [9,10]. Finally, patient data generated within radiation oncology practices is currently residing in separated silos, and has so far not translated into some actionable insights into the best ways of treating patients who are the source of these data.…”
mentioning
confidence: 99%
“…Finally, patient data generated within radiation oncology practices is currently residing in separated silos, and has so far not translated into some actionable insights into the best ways of treating patients who are the source of these data. If such big data can be assembled efficiently and analyzed systematically, great statistical power derived from these largescale population-based analyses can be leveraged to assist in clinical decision making and prediction of treatment outcomes [9,10].…”
mentioning
confidence: 99%
See 1 more Smart Citation